Symbolic calculations of natural voltage balancing dynamics in multilevel flying capacitor converters - Yakupov, R.; Familiant, Y. L.; Ruderman, A. (Nazarbayev University, 2014)
While most of the past research addressed the analysis of natural voltage balancing in Flying Capacitor Converters (FCC) (Fig.1, 2) using frequency domain Fourier based methods, the authors attack the problem in time domain using appropriate averaging methods.
Keywords: symbolic calculations; dynamics; multilevel; converters; voltage balancing; methods